2017
DOI: 10.1016/j.ehj.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics of patients with heart failure and preserved ejection fraction at admission with acute heart failure in Saudi Arabia

Abstract: Heart failure and preserved ejection fraction (HFpEF) is defined as heart failure symptoms and signs with a normal or near-normal ejection fraction (EF) with evidence of diastolic dysfunction. The few Middle Eastern studies that have been conducted were designed to compare patients with heart failure reduced ejection fraction (HFrEF) and HFpEF.The aim of this study was to study Saudi patients with HFpEF who presented with acute heart failure, and define their clinical characteristics and the signs and symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
(78 reference statements)
4
6
0
Order By: Relevance
“…CKD leads to derangements in vascular physiology which in turn yield a bad cardiovascular outcome through abnormal coagulation and fibrinolytic systems, dysfunction of the endothelium, loss of balance between endothelin and nitrogen oxide, electrolyte disturbances that can lead to arrhythmia, and over activation of the sympathetic nervous system and reninangiotensin-aldosterone systems [17]. Furthermore, VHD was noted in 21% of cases and was associated with mortality among the study patients, which is concordant with results from other studies showing a prevalence of 8 % [35], and 13 % [36].…”
Section: Discussionsupporting
confidence: 89%
“…CKD leads to derangements in vascular physiology which in turn yield a bad cardiovascular outcome through abnormal coagulation and fibrinolytic systems, dysfunction of the endothelium, loss of balance between endothelin and nitrogen oxide, electrolyte disturbances that can lead to arrhythmia, and over activation of the sympathetic nervous system and reninangiotensin-aldosterone systems [17]. Furthermore, VHD was noted in 21% of cases and was associated with mortality among the study patients, which is concordant with results from other studies showing a prevalence of 8 % [35], and 13 % [36].…”
Section: Discussionsupporting
confidence: 89%
“…The present study revealed that anemia was common among HF-PEF patients and it was similar to one of the local study (35% in CCU hospitalized patient with HF-PEF) [15] and international study, where 43% of HF-PEF had anemia [23]. Previous studies have also shown that anemia was more common in HF-REF [20,22,24].…”
Section: Table 5: Analysis Of Previous Studiessupporting
confidence: 89%
“…Study Year EF cuttoff for HF-PEF Prevalence Agarwal et al [10] 2001 >50% 19.9% Elshaer et al [11] Elderly inpatients in 2009 >50% 61.8% Khalid et al [12] Inpatients in 2011 >40% 52.2% Alqahtani et al [13] In and out patients in 2012 >55% 25.8% Sulaiman et al [14] Inpatients in 2015 40% 31% Abohammar et al [15] CCU patients >55% 25.8% Present study Outpatients >45% 51%…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anemia in HFpEF patients varies greatly from 15.0% to 79.0% in different reports of different region, different study population, different LVEF and different diagnostic criteria of anemia [2,[12], [13], [14], [15], [16], [17], [18], [19], [20]] (Table 4). The prevalence of anemia in this study was roughly consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%